Tailoring the Adsorption of ACE-Inhibiting Peptides by Nitrogen Functionalization of Porous Carbons - Huettner, Christiane; Hagemann, Diana; Troschke, Erik; Hippauf, Felix; Borchardt, Lars; Oswald, Steffen; Henle, Thomas; Kaskel, Stefan (Langmuir, 2019)
Bioactive peptides, such as isoleucyl-tryptophan (IW), exhibit a high potential to inhibit the angiotensin-converting enzyme (ACE). Adsorption on carbon materials provides a beneficial method to extract these specific molecules from the complex mixture of an α-lactalbumin hydrolysate. This study focuses on the impact of nitrogen functionalization of porous carbon adsorbents, either via pre- or post-treatment, on the adsorption behavior of the ACE-inhibiting peptide IW and the essential amino acid tryptophan (W). The commercially activated carbon Norit ROX 0.8 is compared with pre- and postsynthetically functionalized N-doped carbon in terms of surface area, pore size, and surface functionality. For prefunctionalization, a covalent triazine framework was synthesized by trimerization of an aromatic nitrile under ionothermal conditions. For the postsynthetic approach, the activated carbon ROX 0.8 was functionalized with the nitrogen-rich molecule melamine. The batch adsorption results using model mixtures containing the single components IW and W could be transferred to a more complex mixture of an α-lactalbumin hydrolysate containing a huge number of various peptides. For this purpose, reverse-phase high-pressure liquid chromatography with fluorescence detection was used for identification and quantification. The treatment with the three different carbon materials leads to an increase in the ACE-inhibiting effect in vitro. The modified surface structure of the carbon via pre- or post-treatment allows separation of IW and W due to the certain selectivity for either the amino acid or the dipeptide.
CRIS-Team Scopus Importer:2022-04-14